الحقوق الاقتصادية والاجتماعية في الدول العربية: مفاهيم دستورية وآليات تطبيق - المغبشى، عبدالحكيم عبدالجليل محمد قايد (الرابطة العربية للعلوم البيئية وجامعة الناصر, 2019)
إن ما شهده عالمنا العربي من انتفاضات وثورات شعبية كبيرة، في 2011م اجتاحت معظم الدول العربية، إلا أن أشدها كانت في كل من تونس ومصر واليمن وليبيا، وسوريا، وهي الدول المعنية بالدراسة، ولعل هذه كانت تشبه إلى حد كبير ما جرى في ثمانينات القرن الماضي في دول أوربا الشرقية (الاشتراكية سابقا). وكان الغرض من هذه الثورات واحد في الحالتين، وهو التخلص من الأنظمة المستبدة المتحجرة وإقامة أنظمة ديمقراطية حقيقية تحترم التعددية وحق الاختلاف والتداول السلمي للسلطة ... الخ. وقد نجحت شعوب أوربا الشرقية في نضالها، والآن تتمتع بأنظمة ديمقراطية لا تختلف كثيرا عن تلك التي في أوربا الغربية التي سبقتها في هذا المضمار بعشرات السنين، لذلك نعتقد أنه قد حان الوقت للشعوب العربية أن تلعب ذات الدور، ولا بد من أنها ستنتصر فالتطور سنة الحياة. فبعد أحداث ثورات الربيع العربي سعت هذه الدول المعنية بالدراسة إلى صياغة دساتير جديدة، على ضوء المتغيرات السياسية والاجتماعية والتكنولوجية على الساحة المحلية والدولية، تتضمن ضمانات أساسية لحقوق الإنسان بما فيها الحقوق الاقتصادية والاجتماعية. وتوضيحا لذلك قسمت هذه الدراسة الى خمسة مباحث المبحث الأول تناول المفهوم الاقتصادي والاجتماعي واثرهما على التحول السياسي، وتناول المبحث الثاني، الأطر المرجعية للحقوق الاقتصادية والاجتماعية، وقسم الى مطلبين المطلب الأول تناول الأطر المرجعية الدولية للحقوق الاقتصادية والاجتماعية، وتناول المطلب الثاني الضمانات الأساسية للحقوق الاقتصادية والاجتماعية في الدساتير الجديدة للدول المعنية بالدراسة (تونس مصر اليمن ليبيا سوريا) وتناول المبحث الثالث الحقوق الاقتصادية والاجتماعية في الدساتير الجديدة، وقسم الى مطلبين، الأول استعرضنا فيه الضمانات الدستورية للحقوق الاقتصادية والاجتماعية في الدساتير الخاصة بالدول التي تمت صياغة دساتيرها وأقرتها وعملت بها، كالدستور التونسي والمصري والسوري، وفي المطلب الثاني تنا ولنا فيه دساتير الدول التي صاغت دساتيرها ولم يتم إقرارها حتى الآن، كاليمن وليبيا، وتطرقنا في المبحث الرابع واقع الحقوق الاقتصادية والاجتماعية في الدول المعنية بالدراسة، وفي المبحث الخامس، تحدثنا فيه عن المتطلبات الأساسية للنهوض بالحقوق الاقتصادية والاجتماعية. واشتملت النهاية على الخاتمة واهم النتائج والتوصيات، لعل أهمها: إن هناك نصوص دستورية ضامنة للحقوق الاقتصادية والاجتماعية في دساتير الدول المعنية بالدراس، تتسع في بعضها وتضيق في البعض الآخر، ولكن وجود هذه النصوص في بعض الدساتير، لا يعني أنها دساتير ديمقراطية ، بينما في الواقع يتم تعطيل وتجميد مبادئ الديمقراطية الخاصة بالحريات وحقوق الإنسان، كتعطيل إنفاذ الأحكام الدستورية والقانونية التي تتبنى تلك المبادئ الديمقراطية، وقد يصل الأمر أحيانا إلى خرق الضوابط الدستورية والقانونية الحاكمة في تلك الدول، والتي تحمى حقوق الأفراد في الاقتصاد والصحة والتعليم كما هو في الدول العربية. The Arab world witnessed major popular uprisings in 2011 that dominated Tunisia, Egypt, Yemen, Libya and Syria, the countries which will be the subject of this study. These uprisings are very similar to what happened in the 1980s in the Eastern Europe (formerly socialist countries). The purpose of these revolutions was one of two cases; the elimination of autocratic regimes and the establishment of real democratic systems that observe pluralism, the right of difference, the peaceful transfer of power, etc. The peoples of Eastern Europe have succeeded in their struggle, and now they have democratic systems that are not very different from those in Western Europe preceding them by decades. Therefore, we believe that the time has come for the Arab peoples to play the same role. The current study has been divided into five sections: The first topic dealt with the economic and social concept and its impact on political transformation. The second topic dealt with the reference frameworks for economic and social rights which was divided into two sub-sections. The first was to address international reference frameworks for economic and social rights. The Second was to address the key guarantee of the economic and social rights in the new constitutions of the countries (Tunisia, Egypt, Yemen, Libya, Syria). The third topic dealt with the economic and social rights in the new constitutions. It was divided into two sub-sections: the first tackled the constitutional guarantees of socio-economic rights in the constitutions of the states which drafted and adopted their own constitutions such as the Tunisian , Egyptian and Syrian Constitutions. In the second subsection, we discussed the constitutions of the countries that drafted their constitutions and have not yet adopted them, such as Yemen and Libya. In the fourth section, we discussed the reality of economic and social rights in the studied countries. In the fifth section, we discussed the basic requirements for the promotion of economic and social rights. The study also included a conclusion, results and reommendatoins. The recommendations included the following : there are constitutional provisions that ensure economic and social rights in the Constitutions of the related countries, some of them are widening and in some others narrowing. However, the existence of these texts in some constitutions does not mean that they are democratic constitutions. However, the democratic principles related to freedoms and human rights, such as the enforcement of the constructional and legal rules that adopt such democratic principles, are disrupted . Some other times, the constitutional and legal rules governing those countries, which protect the individuals' economic, social and health rights as it is in the Arab countries are also violated. In fact, these countries have failed to establish a strong economy based on sound scientific research.
Keywords: التشريعات الاقتصادية -- التشريعات الاجتماعية -- حقوق الإنسان -- الاتفاقيات الدولية -- الوطن العربي